Gradient generation platforms: new directions for an established microfluidic technology - Berthier, E. (2014)
Microscale platforms are enabling for cell-based studies as they allow the recapitulation of physiological conditions such as extracellular matrix (ECM) configurations and soluble factors interactions. Gradient generation platforms have been one of the few applications of microfluidics that have begun to be translated to biological laboratories and may become a new “gold standard”. Though gradient generation platforms are now established, their full potential has not yet been realized. Here, we will provide our perspective on milestones achieved in the development of gradient generation and cell migration platforms, as well as emerging directions such as using cell migration as a diagnostic readout and attaining mechanistic information from cell migration models.